Use of Graphic Systems in the Routine of Regular Classroom With a Disabled Student - Deliberato, Débora; Nunes, Leila Regina D’Oliveira Paula (Education Policy Analysis Archives, 2015)
The school environment adapted to the diversity of students is an important goal, but it is a challenge when it comes to the diversity of students with disabilities. The aim of this study was to describe the use of graphics systems in the routine of a preschool classroom through a collaborative program. The study included a teacher, 22 children of a preschool classroom in a school located in a large city in southeastern of Brazil, the mother of a child with disabilities and a special education teacher. A program of collaborative action was carried out among the researcher, the teacher and the students to insert the graphic system in the routine of educational activities for four months. The activities were recorded through a log book, filming and digital recording of interviews. The results obtained from the analysis of the themes identified that the children used the graphic system in the routine of the school tasks, the graphic system helped children in reading the words, the teacher facilitated the insertion of the graphic system from the mediation of the researcher, and the routine of educational activities planned by the teacher facilitated the insertion of the graphic system in the classroom among the students. The study reinforced the need for a training program aimed at school interlocutors to include students with disabilities.